Mismatch in Supply and Demand of Building Surveying Graduates' Skills: A Triangulation Perspective - Husain, Siti Hamidah; Che-Ani, Adi Irfan; Affandi, Haryanti Mohd; Nasri, Nurfaradilla Mohamad; Musid, Nurhafizah Abdul (Journal of Technical Education and Training, 2020)
The mismatch in the supply and demand of graduates is fast becoming a central issue for employee performance nowadays. A primary concern of this issue is a result of a higher competence demanded by employers, the change in the industry, competition among graduates, and new global economic practices. Enabling industries to lead curriculum development is one of the initiatives in enhancing the quality of the programme to improve graduate employability and producing quality technical and vocational education and training (TVET) graduates. Despite the various models that have been employed towards individual career development, there are problems of job skills mismatch and the lack of qualified graduates with technical and non-technical skills. Thus, this study attempts to clarify a mismatch in the supply and demand of building surveying graduates' skills from the perspectives of employers, lecturers, and the students. This study investigates building surveying academicians and the industryâ's perspective regarding building surveying graduates' performance, as well as to identify students' awareness towards the current industry demand. Data for this study was collected using a qualitative method approach that involved a semi-structured interview with 10 building surveying students, 5 lecturers, and 5 building surveyor practitioners; the non-probability sampling design that was used in this study was based on the snowball sampling technique, and a content analysis approach had been employed in the analysis of the data using NVivo 11 software. The findings indicate that there is a mismatch in the supply and demand of building surveying graduates' skills. This study offers an important insight into the building surveying programme towards the improvement of the programme's syllabus and its learning outcomes. The study suggests that building surveying graduates should acquire and demonstrate both technical and non-technical skills that are demanded by the industry. Further research is suggested to identify the competency level among entry-level building surveyor graduates in real working practices.